The Efficacy of the Wellness Program in Enhancing the Health of the Teaching and Non-Teaching Staff in Selected Private Higher Educational Institutions (HEIs) in the Second District of Albay - Edrose Roselada (Philippine Association of Institutions for Research, Inc., 2024)
Employees are the most valuable asset that a company may have since they are the foundation of its success. Their overall health must be cared for to perform at their best. Thus, having a wellness program is a great initiative for any organization. This study evaluated the efficacy of wellness programs on the overall health of teaching and non-teaching staff in selected Private Higher Educational Institutions (PHEIs) in the Second District of Albay. Multimethod design was utilized using structured interviews and survey questionnaires administered to the 192 participants. Findings revealed that the wellness program of the PHEIs has a common purpose and that the activities offered to the staff were also similar. The provision of incentives for employees' improvement is found missing but necessary. The wellness program and physical and mental health were moderately efficient. Although there were some correlations and non-correlations among the respondents regarding the effectiveness of the wellness program on their physical and mental health, these were not statistically significant. Top 3 challenges met by the respondents were lack of engagement, no incentives or awards, and no employee wellness policy. Suggested wellness programs may be adopted and implemented by the three private HEIs under study and other HEIs in the province.